Impaired capillary-to-arteriolar electrical signaling after traumatic brain injury. Issue 6 (June 2021) - Mughal, Amreen; Sackheim, Adrian M; Sancho, Maria; Longden, Thomas A; Russell, Sheila; Lockette, Warren; Nelson, Mark T; Freeman, Kalev
Traumatic brain injury (TBI) acutely impairs dynamic regulation of local cerebral blood flow, but long-term (>72 h) effects on functional hyperemia are unknown. Functional hyperemia depends on capillary endothelial cell inward rectifier potassium channels (Kir2.1) responding to potassium (K + ) released during neuronal activity to produce a regenerative, hyperpolarizing electrical signal that propagates from capillaries to dilate upstream penetrating arterioles. We hypothesized that TBI causes widespread disruption of electrical signaling from capillaries-to-arterioles through impairment of Kir2.1 channel function. We randomized mice to TBI or control groups and allowed them to recover for 4 to 7 days post-injury. We measured in vivo cerebral hemodynamics and arteriolar responses to local stimulation of capillaries with 10 mM K + using multiphoton laser scanning microscopy through a cranial window under urethane and α-chloralose anesthesia. Capillary angio-architecture was not significantly affected following injury. However, K + -induced hyperemia was significantly impaired. Electrophysiology recordings in freshly isolated capillary endothelial cells revealed diminished Ba 2+ -sensitive Kir2.1 currents, consistent with a reduction in channel function. In pressurized cerebral arteries isolated from TBI mice, K + failed to elicit the vasodilation seen in controls. We conclude that disruption of endothelial Kir2.1 channel function impairs capillary-to-arteriole electrical signaling, contributing to altered cerebral hemodynamics after TBI.